User Interface Design Prototype Application Special Onthel Bicycle Tourism in Towilfiets Yogyakarta - Arief Yulianto (Information Technology and Science (ITScience), 2024)
Foreign tourist visits to Yogyakarta, Indonesia have increased in 2022 and 2023 after Covid-19. Many tourists are seeking unique experiences, such as riding on bicycles to enjoy the beautiful scenery and interact with local residents. Towilfiets, a pioneer in onthel bicycle tourism, has been operating in Bantar Hamlet, Kulon Progo for around 10 years. With the growing demand for this activity, Towilfiets needed to innovate their promotion methods, specifically in the digital industry. The development of a user-interface design-based application became crucial to enhance and facilitate the onthel bicycle tourism experience at Towilfiets. The research conducted used a mixed method approach with a phenomenological qualitative method to gather interview data. The prototype method was chosen to allow for intensive and better communication between developers and users. The validation of the questionnaire data was calculated using the Scalable Usage System and received a good score 75 up to score 100 point, indicating acceptable usability. By focusing on user needs and the unique characteristics of tourist destinations, this application aims to increase user engagement and provide relevant and useful information about bicycle tourist attractions in the area. Ultimately, the research aims to develop an innovative and contextualized user interface design application that supports the growth of onthel bike tourism in Towilfiets, located in Dusun Bantar, Kulon Progo, Yogyakarta, Indonesia.